PENGARUH RASIO PELARUT TERHADAP EKSTRAKSI DARI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Amalia Noviyanty; Chitra Anggriani Salingkat; Syamsiar Syamsiar (KOVALEN: Jurnal Riset Kimia, 2019)
This study aims to determine the effect of the ratio of solvents to extract yield, phenolics total and IC50 values ​​of red dragon fruit peel and also get the optimal solvent ratio to obtain extract yield, phenolics total and the highest or best IC50 values ​​of red dragon fruit peel extracts. The solvent ratio used there are 6 levels of the ratio: 2:1; 3:1; 4:1; 5:1; 6:1 and 7:1 (v/w). The data obtained were analyzed using a Completely Randomized Design that was applied to observations of extract yield, phenolics total and IC50 values, if the treatment had a very significant or significant effect followed by continued Tukey HSD test at 1% or 5% level. The results showed that the solvent ratio very significantly affected the extract yield, phenolics total and IC50 value of red dragon fruit peel extract. The solvent ratio of 4:1 (v/w) produced extract yield, phenolics total and IC50 values the highest or best i.e 26.22%, 71.56 ppm, and 124.62 ppm. Keywords : IC50, the red dragon fruit skin, solvent ratio, phenolics total